Evaluación de los procesos productivos mediante la identificación de los puntos críticos de control y su incidencia en la inocuidad de los productos elaborados por la empresa procesadora de alimentos La Picantina - Caisaguano Carrera, Carlos Fabián (2016)
The job have objetive to assess the productive processes for safety to ensure maximum safety of food produced by the food processing company Picantina; the main problem is the direct contact you have is the raw material with the worker for not having personal protective equipment, result-ing in cross-contamination affecting food processing activity; Another problem is that in the pro-cess there are not cleaning procedure necessary for the worker, there is a inadequate lack of clean-liness in the machines, so the plant is not in for the proper conditions for working activities that were identified during the evaluation process. The implemented process previously did not have the appropriate processing hygiene and measures, it is why by studying field is to reduce contam-ination of food, by which it carried out an analysis of critical control points on the basis standards of food safety that help maintain food control in the market, so the health of consumers will be exposed to diseases. To reduce these shortcomings we have make all the above packagins of pro-duction of which shows that research is likely to develop in the company, benefiting not only to the company to position itself in the market, but also by offering a product in optimal conditions for consumption. Where upon they will win not only the owners of the company, but also the human talent that works there and the consumers.